2016
DOI: 10.1007/s11249-016-0719-2
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ski–Snow Tribometer and its Precision

Abstract: Friction between skis and snow was studied in a variety of field and laboratory measurements. Whilst field tests have the drawback of changing conditions, in laboratory tests sport-specific sample sizes and speeds could not be measured up to now. Hence, a novel linear tribometer was developed allowing studies with whole skis at sportspecific speeds. The precision of the tribometer was better than 2.2 %. The dominant cause for the imprecision was the variability of the single snow tracks at lower speed, whilst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 24 publications
3
31
2
Order By: Relevance
“…High static friction argued against pressure melting, whereas system changes that increased interface temperatures (higher ambient temperatures, heat conducted to or trapping at the interface) reduced sliding friction, consistent with their hypothesis. Numerous subsequent studies have produced results consistent with self-lubrication theory, and it remains widely accepted (Evans and others, 1976;Colbeck, 1988Colbeck, , 1992Lehtovaara, 1989;Persson, 2000;Kietzig and others, 2010;Hasler and others, 2016;Nachbauer and others, 2016). Because snow consists of bonded ice grains, studies often assume that self-lubrication prevails on both snow and ice surfaces.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…High static friction argued against pressure melting, whereas system changes that increased interface temperatures (higher ambient temperatures, heat conducted to or trapping at the interface) reduced sliding friction, consistent with their hypothesis. Numerous subsequent studies have produced results consistent with self-lubrication theory, and it remains widely accepted (Evans and others, 1976;Colbeck, 1988Colbeck, , 1992Lehtovaara, 1989;Persson, 2000;Kietzig and others, 2010;Hasler and others, 2016;Nachbauer and others, 2016). Because snow consists of bonded ice grains, studies often assume that self-lubrication prevails on both snow and ice surfaces.…”
Section: Introductionmentioning
confidence: 83%
“…For example, short sliders are proportionally more influenced by dry-contact friction than longer ones, other conditions being the same. Nachbauer and others (2016) and Hasler and others (2016) justified development of a 24 m-long linear tribometer to test full-scale skis in part to avoid this scaling requirement. More complete understanding of the mechanics of each friction mode would aid scaling and lead to models that can predict full-scale performance from reduced-scale tests.…”
Section: Introductionmentioning
confidence: 99%
“…Based on tribometer tests, they suggested that self-lubrication from frictional heating accounted for low kinetic (sliding) friction on both snow and ice substrates. Numerous subsequent studies produced results consistent with self-lubrication theory, and it remains widely accepted (Evans and others, 1976;Colbeck, 1988Colbeck, , 1992Lehtovaara, 1989;Persson, 2000;Kietzig and others, 2010;Nachbauer and others, 2016;Hasler and others, 2016). Because snow consists of bonded ice grains, studies often assume that ice is an acceptable surrogate to study the mechanics of snow friction.…”
Section: Introductionmentioning
confidence: 91%
“…Sliding over fresh ice has been made possible by moving the sliding object over a spiral path [10]. Other tests have used a linear tribometer for measuring the ice friction [11]- [14]. In these situations, the object is not free to move over ice, but is fixed to a mechanism that controls testing conditions (such as load and velocity) and measures the ice friction.…”
Section: Introductionmentioning
confidence: 99%